The Effect of Recent Ethnogenesis and Migration Histories on Perceptions of Ethnic Group Stability - Moya, Cristina (Journal of cognition and culture, 2015)
Several researchers have proposed that humans are predisposed to treat ethnic identities as stable and inherent. However, the ethnographic, historical, and genetic records attest to the ubiquity of inter-ethnic migrations across human history. These two claims seem to be at odds. In this article we compare three evolutionary accounts of how people reason about identity stability, and the effect that the cultural evolution of ethnic group boundaries may have on these beliefs. We test our hypotheses among Himba pastoralists in Namibia, whose recent fission from the neighboring Herero makes them ideal for studying the effect of cultural distance on folk beliefs about identity stability. In a vignette experiment, we asked participants whether an individual born in one group who moved to another group would retain their original group membership and cultural characteristics or acquire those of the new group. Across vignette conditions we examine the importance of the direction of migration, parental social influence, and age at migration on perceptions of identity stability. We also compare participant responses to two out-groups, the Herero, and the more distantly related Damara. We find that participants seldom thought of identity as stable or fixed at birth. Furthermore, we show that cultural distance and endogamous preferences are independent of beliefs of identity stability. Himba believed the Damara character was more likely to change identity and cultural traits than was the Herero character, despite their greater cultural distance from the former group, and despite the fact that all participants expressed more anti-Damara than anti-Herero sentiment.